Construct validity of cadaveric temporal bones for training and assessment in mastoidectomy. (17th April 2015) - Awad, Zaid; Tornari, Chrysostomos; Ahmed, Shahanaz; Tolley, Neil S.
Abstract : Objective: To determine the construct validity of cadaveric temporal bones in mastoidectomy training. Study Design: A prospective observational study. Methods: Trainees from the North London otolaryngology training program performed step‐wise modified radical mastoidectomy on cadaveric temporal bones under faculty supervision. Performance was assessed using a validated mastoidectomy assessment tool. A longitudinal assessment of nine trainees was also carried out over two sessions separated by 12 months. The main outcomes measures were task‐specific (TS) and global skills (GS). Results: Twenty‐six intermediate and eight novice trainees participated and were assessed by a minimum of two assessors each. Intermediate trainees performed significantly better than novices in TS and GS ( P  < 0.001). Performance correlated well with training level using Spearman rank correlation coefficient ( rs ) (TS rs 0.265 and GS rs 0.503). The number of otological procedures performed, and in particular mastoidectomies, correlated well with performance (TS rs 0.327 and GS rs 0.528). Longitudinal assessment showed significant improvement with iteration (TS P  = 0.008 and GS P  = 0.008). Attending otological courses also improved performance significantly (TS rs 0.345 and GS rs 0.469). Conclusions: The cadaveric temporal bone demonstrated construct validity and can be used to detect progress in performance of otolaryngology trainees. This is a keystone in moving toward a competency‐based training system. Level of Evidence: N/A. Laryngoscope, 125:2376–2381, 2015